2012
DOI: 10.1111/j.1365-2672.2012.05317.x
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing activity in Ophiostoma ulmi: effects of fusel oils and branched chain amino acids on yeast-mycelial dimorphism

Abstract: Aims:  For Ophiostoma (Ceratocystis) ulmi, the ability to undergo morphological change is a crucial factor for its virulence. To gain an understanding of quorum‐sensing activity in O. ulmi as it relates to yeast‐mycelium dimorphism control, this study examines the effects of branched‐chain amino acids as well as their fusel alcohols and fusel acids as quorum sensing molecules. Methods and Results:  In a defined medium containing glucose, proline and salts, O. ulmi grew as yeasts when the culture was inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Interestingly, other authors did not find any effect of farnesol on O. ulmi (4,26,33). In this sense, the O. piceae strain studied in this work is a saprophyte and affiliates phylogenetically with the nonpathogenic species of the Ophiostoma clade, such as O. quercus, far from the pathogens O. ulmi and O. novo-ulmi (see Fig.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Interestingly, other authors did not find any effect of farnesol on O. ulmi (4,26,33). In this sense, the O. piceae strain studied in this work is a saprophyte and affiliates phylogenetically with the nonpathogenic species of the Ophiostoma clade, such as O. quercus, far from the pathogens O. ulmi and O. novo-ulmi (see Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Its ability to produce a morphological transition from yeast to hyphal forms, depending on fungal culture conditions, probably contributes to its adaptation to different environmental conditions (3). The effect of inoculum size on culture morphology of fungi from the genera Ophiostoma has been recently reported, suggesting that yeast-or hypha-like growth could be associated with quorum-sensing (QS) activity (4).…”
mentioning
confidence: 99%
“…l-proline was the best N source for yeast production, with the dominant variable being an inoculum size ≥10 7 cells ml -1 . As expected from previous studies on related fungi (Hornby et al 2004;Berrocal et al 2012b), the high cell density which promoted yeast production was mediated by an extracellular lipophilic molecule or group of molecules termed QSMs. The ethyl acetate-extractable supernatants from the albino strain of O. floccosum contained both the biological activity to block mycelial growth and three cyclic sesquiterpenes (Figure 4) as identified by GC/ MS in comparison with the NIST 05 library.…”
Section: Discussionmentioning
confidence: 50%
“…This compound was lipophilic (Hornby et al 2004). Berrocal et al (2012b) found that the addition of 2-methyl-1-butanol or 3-methylvaleric acid (the fusel alcohol and fusel acid derived from isoleucine, respectively) or 4-hydroxyphenylacetic acid decreased the formation of germ tubes in O. ulmi cultures by more than 50%, thus demonstrating a QSM behavior. A similar effect was obtained using branched-chain amino acids (precursors of fusel alcohols) as N sources (Berrocal et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation